Hijab: From Legal Aspects to Individual Piety - Lutfi Zarkasi; Sahrandi, Akhmad (Program Pascasarjana Institut Agama Islam (IAI) Darullughah Wadda'wah Pasuruan, 2022)
Hijab is an obligation commanded by Allah which is clearly explained in the Qur'an. Judging from the use of the Hijab as the purpose of covering the genitals will affect the religious behavior of women. The obligation to wear the hijab for Muslim women should be improved and it is necessary to deepen the true meaning of the hijab for Muslim women in its implementation in everyday life. Muslim women should pay more attention to, improve and exemplify the use of the hijab based on noble behavior and morals. In this way, the hijab does not only speak of law but also relates to individual piety. Therefore, guidance, direction, examples and knowledge are needed for women so that they can implement the obligation to wear the hijab properly and consistently in its use, so that good morals and behavior will follow automatically.